Solve for x
x=\frac{\sqrt{2480645}-1575}{2}\approx 0.003174597
x=\frac{-\sqrt{2480645}-1575}{2}\approx -1575.003174597
Graph
Share
Copied to clipboard
x^{2}+1575x=5
Multiply 25 and 63 to get 1575.
x^{2}+1575x-5=0
Subtract 5 from both sides.
x=\frac{-1575±\sqrt{1575^{2}-4\left(-5\right)}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, 1575 for b, and -5 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-1575±\sqrt{2480625-4\left(-5\right)}}{2}
Square 1575.
x=\frac{-1575±\sqrt{2480625+20}}{2}
Multiply -4 times -5.
x=\frac{-1575±\sqrt{2480645}}{2}
Add 2480625 to 20.
x=\frac{\sqrt{2480645}-1575}{2}
Now solve the equation x=\frac{-1575±\sqrt{2480645}}{2} when ± is plus. Add -1575 to \sqrt{2480645}.
x=\frac{-\sqrt{2480645}-1575}{2}
Now solve the equation x=\frac{-1575±\sqrt{2480645}}{2} when ± is minus. Subtract \sqrt{2480645} from -1575.
x=\frac{\sqrt{2480645}-1575}{2} x=\frac{-\sqrt{2480645}-1575}{2}
The equation is now solved.
x^{2}+1575x=5
Multiply 25 and 63 to get 1575.
x^{2}+1575x+\left(\frac{1575}{2}\right)^{2}=5+\left(\frac{1575}{2}\right)^{2}
Divide 1575, the coefficient of the x term, by 2 to get \frac{1575}{2}. Then add the square of \frac{1575}{2} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+1575x+\frac{2480625}{4}=5+\frac{2480625}{4}
Square \frac{1575}{2} by squaring both the numerator and the denominator of the fraction.
x^{2}+1575x+\frac{2480625}{4}=\frac{2480645}{4}
Add 5 to \frac{2480625}{4}.
\left(x+\frac{1575}{2}\right)^{2}=\frac{2480645}{4}
Factor x^{2}+1575x+\frac{2480625}{4}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{1575}{2}\right)^{2}}=\sqrt{\frac{2480645}{4}}
Take the square root of both sides of the equation.
x+\frac{1575}{2}=\frac{\sqrt{2480645}}{2} x+\frac{1575}{2}=-\frac{\sqrt{2480645}}{2}
Simplify.
x=\frac{\sqrt{2480645}-1575}{2} x=\frac{-\sqrt{2480645}-1575}{2}
Subtract \frac{1575}{2} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}